2005
DOI: 10.1200/jco.2005.04.120
|View full text |Cite
|
Sign up to set email alerts
|

Switching to Anastrozole Versus Continued Tamoxifen Treatment of Early Breast Cancer: Preliminary Results of the Italian Tamoxifen Anastrozole Trial

Abstract: Switching to anastrozole after the first 2 to 3 years of treatment is well tolerated and significantly improves event-free and recurrence-free survival in postmenopausal patients with early breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
293
3
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(314 citation statements)
references
References 29 publications
10
293
3
5
Order By: Relevance
“…[2][3][4] Although tamoxifen has been the cornerstone of treatment for hormone-sensitive early breast cancer, recently reported randomized clinical trials (RCTs) clearly indicate the benefit of AI. [5][6][7][8][9][10][11][12][13][14][15] These benefits, despite strategic differences across RCTs and patient populations, are consistent with all AIs, and previously reported cumulative analyses have indicated that there is an overall survival benefit to the already documented advantage in diseasefree survival (DFS). 7,14 Despite these positive aspects, toxicity profile and the pharmacoeconomic aspects should always be taken into account when discussing new treatment strategies, particularly in the presence of small benefits.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…[2][3][4] Although tamoxifen has been the cornerstone of treatment for hormone-sensitive early breast cancer, recently reported randomized clinical trials (RCTs) clearly indicate the benefit of AI. [5][6][7][8][9][10][11][12][13][14][15] These benefits, despite strategic differences across RCTs and patient populations, are consistent with all AIs, and previously reported cumulative analyses have indicated that there is an overall survival benefit to the already documented advantage in diseasefree survival (DFS). 7,14 Despite these positive aspects, toxicity profile and the pharmacoeconomic aspects should always be taken into account when discussing new treatment strategies, particularly in the presence of small benefits.…”
mentioning
confidence: 59%
“…Seven trials (19,818 patients) were identified that were eligible for inclusion in this analysis 5,6,8,[10][11][12][13]15,25 ( Fig. 1).…”
Section: Selected Trialsmentioning
confidence: 99%
“…Ovarian ablation, as an adjuvant therapy, has been demonstrated to lead to longer survival in premenopausal patients [4]. Aromatase inhibitors have also shown efficacy in reducing the risk for recurrence and/or death in postmenopausal patients with hormone-responsive early breast cancers [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…For many years, tamoxifen was the cornerstone of endocrine therapy with a substantial body of evidence showing benefits in overall survival [1]. However, more recently, trials of AIs have shown benefits over tamoxifen, in both a metastatic [2][3][4] and subsequent adjuvant treatment setting [5][6][7][8][9][10][11]. The main advantages have been improvements in disease free survival and a more favourable toxicity profile, with lower rates of thromboembolic phenomena and endometrial malignancy.…”
Section: Introductionmentioning
confidence: 99%